Ambivalence in the (Private) Public Sphere: How Global Digital Activists Navigate Risk - West, Sarah Myers (AoIR Selected Papers of Internet Research, 2016)
This study examines the accounts of a global network of digital activists to understand how they view their relationships with social media platforms and negotiate risk in digital environments. Through semi-structured interviews with a geographically diverse group of activists, all of whom write for the citizen media platform Global Voices, the paper considers how the activists negotiate an ambiguous and shifting landscape of online threats in the conduct of their work. It uncovers a deep vein of ambivalence around digital practices, particularly with regard to the role of social media companies. It also aims to contribute a better comparative understanding of risk across a number of digital environments: surveillance and censorship take different forms and are experienced in different ways depending on the activists’ geography. I find while activists are innovatively using these platforms to create new spaces for speech and dissent, they are also spaces of ambiguity and ambivalence, and may be as dangerous as they are generative. I explore the forms of user agency taken up by activists as they negotiate networked privacy in the (private) public sphere.